Learn, move, compete: an alternative approach to mini tennis lessons - Wigham, Matt; Wheatley, Simon (ITF Coaching & Sport Science Review, 2023)
In this article, we look at how competition is presented in the traditional mini tennis lesson, finding that it typically occurs once, at the end of the session. We then explore some of the limitations associated with competition in this format. Following that, we discuss the importance of developing competitive capabilities, and propose an alternative way of approaching the mini tennis lesson to provide more opportunity for competition while systematically developing tactical and technical skills in a manner consistent with findings from skill acquisition research. This methodological approach, we suggest, provides a more fertile environment in which to develop competitive performers alongside the tactical and technical performance factors.